Shifting goals: effects of active and observational experience on infants’ understanding of higher order goals - Gerson, Sarah A.; Mahajan, Neha; Sommerville, Jessica A.; Matz, Lauren; Woodward, Amanda L. (Frontiers in Psychology, 2015)
Action perception links have been argued to support the emergence of action understanding, but their role in infants’ perception of distal goals has not been fully investigated. The current experiments address this issue. During the development of means-end actions, infants shift their focus from the means of the action to the distal goal. In Experiment One, we evaluated whether this same shift in attention (from the means to the distal goal) when learning to produce multi-step actions is reflected in infants’ perception of others’ means-end actions. Eight-months-old infants underwent active training in means-end action production and their subsequent analysis of an observed means-end action was assessed in a visual habituation paradigm. Infants’ degree of success in the training paradigm was related to their subsequent interpretation of the observed action as directed at the means versus the distal goal. In Experiment Two, observational and control manipulations provided evidence that these effects depended on the infants’ active engagement in the means-end actions. These results suggest that the processes that give rise to means-end structure in infants’ motor behavior also support the emergence of means-end structure in their analysis of others’ goals.